The Role Of Supply Chain Management (SCM) On MSME Performance Using BibliometricI Analysis - Nurleli Nurleli; Ririn Sri Kuntorini; Elly Halimatusadiah; Irena Pramita Pramono (Kajian Akuntansi, 2022)
UMKM tahu daerah Ciburial sudah menjalankan sebagian dari SCM, yaitu selalu memilih bahan kedelai yang berkualitas. Akan tetapi, UMKM tahu Ciburial ini belum melakukan kerja sama yang rutin dengan konsumen dalam jumlah yang banyak meskipun sebenarnya sudah ada kerja sama,  di antaranya dengan Food Court Jogya Departemen Store. Dalam hal ini, regulasi pemerintah dalam penyediaan bahan baku yang murah dan berkualitas sangat diperlukan mengingat tahu adalah makanan masyarakat menengah ke bawah sehari-hari. Program Studi Akuntansi dalam hal ini Fakultas Ekonomi dan Bisnis Unisba melakukan kerja sama dalam meningkatkan volume tahu yang terjual. Selanjutnya, perlu adanya regulasi pemerintah dalam kesediaan bahan baku tahu agar sustainability UMKM Tahu tetap berlangsung. The importance of the role of MSMEs in the Indonesian economy makes this sector can not be underestimated and the progress of this sector will be the focus of the government for the next few years. Classic problems related to distribution often occur in micro, small and medium scale enterprises. So it is hoped that with the Supply Chain Management (SCM), problems related to distribution can be overcome. Therefore, this study intends to examine how the role of SCM in the progress of MSMEs. The method used in this study is a qualitative research method with a literature study approach using bibliometric analysis. The software used is Vosviewer with a number of articles collected from Crossref over the last 5 years, using the keywords: “Supply chain management” and “small medium enterprises”. The results of the study show that SCM in MSMEs will be related to efforts to create sustainability, increase competitive advantage, and improve the quality of relationships with customers.